Recent progress in thiocarbazone metal complexes for cancer therapy via mitochondrial signalling pathway - Zheng, Yunyun; An, Hangyi; Qi, Jinxu; Li, Jiaming (Frontiers in Chemistry, 2024)
Mitochondria are the energy factories of cells and are important targets for the development of novel tumour treatment strategies owing to their involvement in processes such as apoptosis, oxidative stress, and metabolic programming. Thiosemicarbazone metal complexes target mitochondria and reduce mitochondrial membrane potential. The breakdown of mitochondrial membrane potential is a key event in the early stage of apoptosis, which releases cytochrome C and other pro-apoptotic factors, activates the intracellular apoptotic enzyme cascade, and eventually causes irreversible apoptosis of tumour cells. Thiosemicarbazone metal complexes targeting the mitochondria have recently emerged as potential antitumour agents; therefore, this review describes the structural diversity of thiosemicarbazone metal (Fe(III), Cu(II), Ni(II), Zn(II), Ga(III), Pb(II), Au(III), and Ir(III)) complexes and explores their anti-tumour mechanisms that target mitochondrial pathways.